?pm (?) - Statistical Convergence of Order ? - Altin, Yavuz; Et, Mikail; Altinok, Hifsi (Amer Inst Physics, 2018)
In this study, using the generalized difference operator Delta(m) and a sequence lambda = (lambda(n)) is a non -decreasing sequence of positive numbers tending to oo such that lambda(n+1) <= lambda(n) + 1, lambda(1) = 1, we generalize the concepts of statistical convergence of order a and p Cesaro summability of order a and give some relations connected to these concepts.
7th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 28-31, 2018 -- Kyiv, UKRAINE
Keywords: Sequence Space; Beta; Sets